Pembekalan Strategi Manajemen dalam Menghadapi Tantangan Perekonomian Usaha di Era Digital - Zakiatul Hidayah, Zulfa; Soleha, Erin; Latif, Abdul; Hariroh, Fiqih Maria Rabiatul; Meirani, Nadia (Abdimas Indonesian Journal, 2024)
Field surveys were used in this Community Service initiative to gain further understanding of customer preferences, market trends, and areas of improvement needed by their companies. The devotion team managed to obtain important information from customers and business owners during the initial interviews to analyze the problems faced. A number of solutions were created to improve Angkringan's business performance once the problems were identified. Improvements in finance, marketing, promotion, expansion of premises and facilities, better sales strategies, product innovation, better customer service, and customer relationship maintenance are some examples of such actions. It is expected that these activities will improve service quality, increase customer satisfaction, and increase market share. This will help the business stay relevant and compete in a competitive market while enhancing customer relationships and improving overall business performance.